2001
DOI: 10.1152/ajprenal.2001.280.2.f223
|View full text |Cite
|
Sign up to set email alerts
|

Role of 20-HETE in mediating the effect of dietary K intake on the apical K channels in the mTAL

Abstract: We have used the patch-clamp technique to study the effect of dietary K intake on the apical K channels in the medullary thick ascending limb (mTAL) of rat kidneys. The channel activity, defined by the number of channels in a patch and the open probability (NPo), of the 30- and 70-pS K channels, was 0.18 and 0.11, respectively, in the mTAL from rats on a K-deficient diet. In contrast, NPo of the 30- and 70-pS K channels increased to 0.60 and 0.80, respectively, in the tubules from animals on a high-K diet. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
18
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 34 publications
5
18
0
Order By: Relevance
“…Because the Ca 2ϩ -sensing receptor is located in the basolateral membrane of the mTAL, it is conceivable that the stimulation of the Ca 2ϩ -sensing receptor may also inhibit the basolateral 50-pS K channel. Moreover, we have previously demonstrated that 20-HETE production increased in the mTAL obtained from rats on a K-deficient diet (12). Therefore, it is possible that basolateral K channel activity differs between mTALs from animals on a normal-K diet and from those on a low-K diet.…”
Section: Discussionmentioning
confidence: 95%
“…Because the Ca 2ϩ -sensing receptor is located in the basolateral membrane of the mTAL, it is conceivable that the stimulation of the Ca 2ϩ -sensing receptor may also inhibit the basolateral 50-pS K channel. Moreover, we have previously demonstrated that 20-HETE production increased in the mTAL obtained from rats on a K-deficient diet (12). Therefore, it is possible that basolateral K channel activity differs between mTALs from animals on a normal-K diet and from those on a low-K diet.…”
Section: Discussionmentioning
confidence: 95%
“…However, these results are confounded because heme oxygenase inducers also stimulate the formation of the vasodilatory gas carbon monoxide and may influence nitric oxide synthase activity and produce vasodilatory factors via the cGMP pathway (35). Dibromo-olefinic fatty acids are relatively specific inhibitors of arachidonic acid -/( -1)-hydroxylation and have been extensively used to characterize 20-HETE biological effects in vitro and in situ (17,21,46,54). The most potent inhibitor of arachidonic acid -hydroxylation to date is N-hydroxy-NЈ-(4-butyl-2-methylphenyl)-formamidine (HET-0016) (33).…”
Section: Discussionmentioning
confidence: 99%
“…20-HETE and EETs have effects on thick ascending limb (TAL) cells that decrease sodium reabsorption. The inhibitory action of 20-HETE on Na ϩ transport in the TAL is associated with closure of the apical 70-pS K ϩ channels (10,50). AA also inhibits the 50-pS K ϩ channels in the basolateral membrane of the mTAL mainly through cytochrome P-450-dependent metabolites of AA (11).…”
mentioning
confidence: 99%